Perancangan Sistem Informasi Akuntansi Berbasis Vb. Net Di PT. Indoland Development - Tholib Hariono; Fitri Astutik; Chairul Anam (Unit Publikasi dan Jurnal Universitas KH. A. Wahab Hasbullah, 2019)
Accounting Information System (SIA) is a program used to assist the processing of corporate financial data which is applied to PT.Indoland Development with the aim to improve the quality of recording and account corporate finance so that they will be more precise and accurate.Purpose this study is determine the effectiveness and Efficiency of Accounting Information System of company performance in PT.Indoland Development. In this company recording and reporting activities are still somewhat manual that just using microsoft word or microsoft excel even sometimes still have to write manual with pen and book. From the research is expected to provide input on PT.Indoland Development in order to further improve the quality of the company with the Accounting Information System that has been made. In this research, researchers try to create Accounting Information System in PT.Indoland Development. In the making using Visual Basic .NET (VB .NET), which designed the creation of systems with the application of the foundations in the science of accounting. The results showed that the company director gave a good response to the Effectiveness and Efficiency of Accounting Information Systems, with Accounting Information System. VB .NET-based This recording and financial reports in the company more effective and efficient. Accounting Information System used will make the recording and financial reporting better so that the quality of the company will increase.